Remote ECG Monitoring Using Arduino Application - Fadhil, Waleed Khalid; Hasan Ali, Hussein; Hadi, Basheer Hashim (American Journal of Botany and Bioengineering, 2024)
This ECG project relies on a sensor for data acquisition, leveraging technology and programming for its design. It involves thorough research into modern ECG technologies and user requirements. The project encompasses designing, prototyping, and testing the system to ensure precise cardiac monitoring and user-friendly functionality. Key considerations include user comfort, portability, and compatibility with existing medical equipment. Moreover, the integration of advanced technologies and programming techniques facilitates real-time data analysis, remote monitoring capabilities, and customizable features tailored to individual patient needs. Ultimately, the project aims to advance diagnostic accuracy, treatment planning, and overall cardiac health outcomes through the seamless fusion of hardware, software, and medical expertise, while ensuring the highest standards of patient confidentiality and privacy.